(3GdfGSN hGdefShN (B( (3aj cJGH Gddg YR hLd hGNJdGa GdYdeGA aj Pdc (B)s - (3CHh LYaQ CMeO Hf eMeO Hf ESeGYjd Hf GdUZGQ GdfMhjs
(3ChdgG (B:s
(3bGd MOKfG GdTjN CHh GdbGSe YHO GdQMef Hf eMeO Hf Ydi Hf CMeO GdCOahi bGd MOKfi CHj bGd fHJOF ai gPG GdcJGH hgh cJGH GdfGSN hGdefShN HMeO Gddg GdhGMO GdLHGQ s
(3BNQgG (B:s
(3hai GdCeQ hGdfgi CjVkG eGdGjbY ajg fSN hPdc GdCeQ HJhMjO Gddg Ld KfGDg hEJHGY QSdg Udi Gddg Ydjg hSde fHi GdQMeI HGdUdGI hGdJSdje hCgdg GdWjHjf Je GdcJGH s
(3fSNI fajSI LOkGs
(3YhQV HCUd Ydjg NW GdMGaX GdefPQis
(3hSeGYGJ YOjOI ef GdbQf GdNGeSs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs